Impact of sense of coherence on work ability: A cross-sectional study among Croatian nurses - Smrekar Martina; Zaletel-Kragelj Lijana; Franko Alenka (Sciendo, 2022)
Aimed at preparing the basis for planning evidence-based public health measures for preservation/ improvement of nurses' work ability (WA), the objective was to assess the relationship between WA and sense of coherence (SOC).